Polish national character in the context of state defence - Komorowski Krzysztof (2021)
Objective: Demonstration and analysis of the impact of the human factor on the effectiveness of the state defence system. Material and Methods Literature research and critical analysis Results The research demonstrates that the human factor is the most important component of the state defence potential. This thesis is corroborated by examples from the history of Poland, and supported with philosophical, ethical and ethnographic considerations. Based on the examination of the selected research group consisting of Polish soldiers, qualities important for Poles, such as honour, righteousness and patriotism, which are at the foundation of the national character of a soldier, have been identified. On the other hand, the article also takes into account negative stereotypes and opinions presented in the literature regarding the national character of the Polish soldier. Conclusions The conducted research and analysis prove the unquestionable domination of the human factor in state defence and military systems. It has been shown that, apart from the demographic potential and mobilisation capabilities, an important aspect of the human factor for defence is the national character and the morale of the army, which should be prioritised over material aspects. Honour, both in the axiological dimension of the sense of pride, dignity, nobility, and diligence, as well as in the sense of an ethical virtue in people's mentality and the morale of soldiers, shapes consciously determined attitudes and behaviours.